Inter-relay cooperation - Abou-Rjeily, Chadi (2016)
In this paper, we study the effect of the presence of inter-relay connections on the performance of cooperative free-space optical (FSO) networks. Unlike the existing literature where conventional cooperation in FSO systems is realized in two steps through source-relay (S-R) followed by relay-destination (R-D) communications, we propose and analyze a novel three-stage cooperation methodology. The proposed scheme is based on exploiting the potential presence of FSO links between neighboring relays for the sake of complementing the S-R and R-D steps with an intermediate inter-relay communication step that serves in enhancing the fidelity of signal reconstruction at the relays before retransmitting to the destination. For the proposed scheme, we derive closed-form expressions for the conditional error probability with any number of relays. We also propose a closed-form power allocation strategy (PAS) in the case where the background noise is negligible. This PAS is based on minimizing an asymptotic upper-bound on the conditional error probability by applying the method of Lagrange multipliers with the solution satisfying the Karush-Kuhn-Tucker (KKT) conditions. Results show that the presence of inter-relay connections, associated with an appropriate cooperation scheme and PAS, can significantly boost the performance of relay-assisted FSO systems.